2015
DOI: 10.1111/pcmr.12434
|View full text |Cite
|
Sign up to set email alerts
|

Rab9A is required for delivery of cargo from recycling endosomes to melanosomes

Abstract: Melanosomes are a type of lysosome-related organelle that is commonly defective in Hermansky–Pudlak syndrome. Biogenesis of melanosomes is regulated by BLOC-1, -2, -3, or AP-1, -3 complexes, which mediate cargo transport from recycling endosomes to melanosomes. Although several Rab GTPases have been shown to regulate these trafficking steps, the precise role of Rab9A remains unknown. Here, we found that a cohort of Rab9A associates with the melanosomes and its knockdown in melanocytes results in hypopigmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 52 publications
(141 reference statements)
3
29
0
Order By: Relevance
“…10). Consistent with our results, very recently, during the course of revising this paper, Mahanty et al (36) have reported the involvement of Rab9A in melanogenic enzyme trafficking. Moreover, we demonstrated that RUTBC1 is able to disrupt the interaction between Rab9A and HPS4, a component of BLOC-3, a Rab32/38 GEF (12) (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…10). Consistent with our results, very recently, during the course of revising this paper, Mahanty et al (36) have reported the involvement of Rab9A in melanogenic enzyme trafficking. Moreover, we demonstrated that RUTBC1 is able to disrupt the interaction between Rab9A and HPS4, a component of BLOC-3, a Rab32/38 GEF (12) (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, a recent report has demonstrated that the Rab9-RUTBC1 complex is required for the trafficking of melanogenic enzymes in melanocytes (Marubashi et al, 2016). In line with this, Rab9 has been shown to be involved together with the biogenesis of lysosome-related organelles complex 3 (BLOC-3), another Rab9 effector, in syntaxin-13-mediated cargo transport from early endosomes to maturing melanosomes (Mahanty et al, 2016). Therefore, a new role of Rab9 as a mediator of the transport towards lysosomes or lysosome-related organelles, such as melanosomes, is now beginning to emerge.…”
Section: Rab9mentioning
confidence: 71%
“…In a recent study, we have shown that Rab9A functions in targeting REs towards melanosomes . Thus, we evaluated the regulatory role of Rab9A along with Rab7A, 11A and 22A on RE dynamics in HeLa cells.…”
Section: Resultsmentioning
confidence: 98%